A comprehensive review of recent advances in renewable-based drying technologies for a sustainable future. Issue 6 (2nd May 2022) - Acar, Canan; Dincer, Ibrahim; Mujumdar, Arun
Abstract: Conventional drying technologies generally rely on drying processes driven by using hot air, where these processes have significantly high energy consumption and greenhouse gas emissions. With our knowledge based on the limited nature of fossil fuels and the impact of climate change, it is clear that every technology has to be cleaner, cheaper, and more efficient to limit our carbon footprint while maintaining sustainable development. In this regard, the present study comprehensively reviews the recent advances in drying technologies and energy consumption and the efficiency and economic performances of several alternative drying technologies. The reviewed drying technologies include adsorption mediated, agitated thin film, electrotechnologies, hybrid systems, impingement, heat pumps, microwave, ohmic-heating, refractance window, rotating drum, superheated steam, and vacuum. The selected performance criteria are final heat use, final electricity use, primary energy use, thermal and energy efficiencies, and operating cost. With these criteria taken into account, the results show that the refractance window has the highest sustainability ranking (8.28/10), and superheated steam has the lowest sustainability ranking (2.90/10). Besides, the sustainability of the different drying fuels and technologies is conducted, and the results show that renewables have the highest sustainability ranking. Besides, it is seen that some novel approaches in drying, such as solar-based hybrid drying systems and refractance window drying, are amongst the most promising sustainable technologies. They could be the key to clean, affordable, reliable, and efficient drying of different kinds of products in industrial processes.